2023
DOI: 10.1111/jre.13152
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial dysfunction in periodontitis: From mechanisms to therapeutic strategy

Abstract: Periodontitis is an inflammatory and destructive disease of tooth‐supporting tissue and has become the leading cause of adult tooth loss. The most central pathological features of periodontitis are tissue damage and inflammatory reaction. As the energy metabolism center of eukaryotic cells, mitochondrion plays a notable role in various processes, such as cell function and inflammatory response. When the intracellular homeostasis of mitochondrion is disrupted, it can lead to mitochondrial dysfunction and inabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…5 Overall effects of metal exposures on periodontitis in the subgroups with different smoking status. A Non-smokers (without tobacco exposure), B second-hand smokers, C smokers malfunction and induced mitochondrial DNA mutations [51], which induce excessive production of ROS [52] in mitochondria, causing oxidative phosphorylation dysfunction and cellular apoptosis through MAPK pathway [53], which exacerbate biological aging in periodontal tissues [54]. Furthermore, previous animal experiments have shown that excessive ROS is strongly associated with alveolar bone resorption in rats [55].…”
Section: Discussionmentioning
confidence: 99%
“…5 Overall effects of metal exposures on periodontitis in the subgroups with different smoking status. A Non-smokers (without tobacco exposure), B second-hand smokers, C smokers malfunction and induced mitochondrial DNA mutations [51], which induce excessive production of ROS [52] in mitochondria, causing oxidative phosphorylation dysfunction and cellular apoptosis through MAPK pathway [53], which exacerbate biological aging in periodontal tissues [54]. Furthermore, previous animal experiments have shown that excessive ROS is strongly associated with alveolar bone resorption in rats [55].…”
Section: Discussionmentioning
confidence: 99%
“…This article will not discuss the pathogenesis of periodontitis and associated conditions, on which there are many excellent papers [ 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 ], but we must present, in short, the most significant cellular and molecular changes affecting the periodontal ECM, causing anatomical disturbances.…”
Section: The Extracellular Matrix Of the Periodontium And The Role Of...mentioning
confidence: 99%
“…Previous research has also demonstrated that periodontitis is closely associated with MD. Multiple investigations have revealed that periodontitis patients have increased ROS production, a reduced level of adenosine triphosphate (ATP), and a reduced mitochondrial membrane potential (MMP), resulting in cell mortality in the periodontium and inhibition of tissue regeneration [12,32]. MD is caused by an unbalanced internal environment in the periodontal tissue [23].…”
Section: Introductionmentioning
confidence: 99%